INSTITUTE OF SCIENCE OF MACHINES AND METALLURGY DVO RAN INCREASING OF EXACTNESS OF POROUS MODELS IN CASTING BY INVESTMENT PATTERNS - I. G. Sapchenko; S. G. Zhilin; O. N. Komarov (Литьë и металлургия)
Тhе influence of new technology of the porous models production of traditional wax-like smelted materials on dimensional and geometric accuracy of these models is studied.